2016
DOI: 10.1515/jpm-2015-0421
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum is associated with increased maternal serum ischemia-modified albumin

Abstract: We found that HEG was related to increased maternal serum IMA levels. HEG might be due to an ischemic intrauterine environment leading to elevated serum IMA concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
3
6
2
2
Order By: Relevance
“…[8] However, in some studies, no change in lymphocyte count has been shown. [1319] In our study, the lymphocyte count was found to be lower in the HEG group, which was consistent with other studies from the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[8] However, in some studies, no change in lymphocyte count has been shown. [1319] In our study, the lymphocyte count was found to be lower in the HEG group, which was consistent with other studies from the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Sari et al . [19] found that Hb and hematocrit levels did not change in HEG patients. These findings were similar in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For other conditions (obstructive sleep apnoea syndrome [128] , ovarian torsion [129] , mothers bearing small-for-gestational-age foetuses [116] and preterm babies with respiratory distress syndrome [130] ), FFA levels have not yet been measured. Several other studies detected higher IMA levels in yet more conditions (hyperemesis gravidarum [131] , perinatal asphyxia [132] , mild cognitive impairment [133] , pre-eclampsia [90] ), however they were not included in our analysis as “IMA levels” were measured with an immunoassay (see next section) instead of the ACB assay.…”
Section: Ischemia-modified Albumin In Disease Statesmentioning
confidence: 99%
“…Gebelik döneminde gözlenen komplikasyonlarla oksidatif stres arasındaki ilişkiyi gösteren çok sayıda çalışma mevcuttur (6,7). Fait ve ark.…”
Section: Introductionunclassified
“…Düşük glutatyon seviyesi HEG'deki oksidatif stresin bir kanıtı olarak değerlendirilmiştir. Buna benzer şekilde HEG'de artmış oksidatif stres kanıtları gün geçtikçe artarak devam etmiş, ancak bunun aksini gösteren çalışmalar da literatürde kendine yer bulabilmiştir (1,7,9). Tüm bu bulgular birlikte değerlendirildiğinde HEG patogenezinde oksidatif stresin rolünü net bir şekilde söylemek halen mümkün değildir.…”
Section: Introductionunclassified